Activated carbon-based electrodes for two-steps catalytic/ electrocatalytic reduction of glycerol in Amberlyst-15 mediator. (May 2022) - Md Rahim, Siti Aqilah Nadhirah; Lee, Ching Shya; Abnisa, Faisal; Wan Daud, Wan Mohd Ashri; Aroua, Mohamed Kheireddine; Cognet, Patrick; Pérès, Yolande
Abstract: Redox mediators supply an effective way to promote electrons (and protons) transport between the electrode and substrate without being in direct physical contact with the electrode. Here, the carbon-based electrodes with Amberlyst-15 as the redox mediator were used in the electrocatalytic reduction to investigate their ability to indirectly convert glycerol into 1, 2-propanediol. The process aims to study the influence of different activated carbon compositions (60%, 70%, 80%, and 90% of total weight) in the activated carbon composite (ACC) electrodes on the electrochemical properties, reaction mechanisms, and selectivity of the yielded products. Their electrochemical behavior and physicochemical properties were determined by cyclic voltammetry (CV) and chronoamperometry (CA), followed by FESEM-EDX for the selected ACC electrode. Electroactive surface area (EASA) plays a role in glycerol mass transport and electrons transfer. EASA of 60ACC, 70ACC, 80ACC, and 90ACC (geometrical surface area of 0.50 cm 2 ) were 19.62, 24.50, 36.74 and 30.83 cm 2, respectively. With the highest EASA, 80ACC enhanced the mass transport and electrons transfer process that eventually improved its electrocatalytic activity. It outperformed other ACC electrodes by generating Amberlyst-15 radicals (A-15 - ) with high current density at low potential (−0.5 V vs. Ag/AgCl). A-15 - served as the electron-donor for the homogeneous redox reaction with glycerol in delivering highly reactive glycerol radical for further intermediates development and generated 1, 2-propanediol at −2.5 V vs. Ag/AgCl (current density of −0.2018 A cm −2 ). High activated carbon content portrayed a dominant role in controlling EASA and favored consecutive acetol-1, 2-propanediol production through the C–O bond breakage. From the galvanostatic electrolysis, 1, 2-propanediol selectivity was higher on 80ACC (88.6%) compared to 60ACC (61.4%), 70ACC (70.4%) and 90ACC (72.5%). Diethylene glycol formation was found to be the side reaction but preferred low activated carbon percentage in 60ACC and 70ACC. Graphical abstract: Image 1 Highlights: High activated carbon percentage exhibited high electroactive surface area. Amberlsyt-15 aided the electrons transfer between the electrodes and glycerol. 80ACC displayed the best performance of electrocatalytic reduction of glycerol. The initial steps for the reaction are C–O and C–C bonds cleavage of glycerol.